The Relationship Between Exclusive Breastfeeding and Allergic Manifestations Among Toddlers at Sawah Lebar Public Health Center - Tari Puspita; Devi Cynthia Dewi; Ardiana Podesta (POLTEKKES KEMENKES BENGKULU, 2026)
BackgroundAllergic manifestations in toddlers continue to increase and are influenced by several factors, including exclusive breastfeeding. Allergy is a specific immune system reaction to substances called allergens, which may trigger different responses in different individuals. Allergic reactions are hypersensitivity responses initiated through immunological mechanisms involving Immunoglobulin E (IgE) bound to mast cells after exposure to allergens. Allergies frequently occur in toddlers because their immune systems are still immature and vulnerable. The highest incidence of allergies in children aged 2–5 years is associated with food and inhalant allergens. Several factors are suspected to influence allergic manifestations in children, one of which is breastfeeding. Previous studies have shown that exclusive breastfeeding may reduce the occurrence of allergic diseases in children. ObjectiveThis study aimed to analyze the relationship between exclusive breastfeeding and allergic manifestations in toddlers. MethodsA cross-sectional study was conducted among 97 toddlers using consecutive sampling and Chi-square analysis. The study sample consisted of toddlers aged 2–60 months. ResultsThe study involved 97 toddlers, of whom 37 toddlers (34.1%) experienced allergic manifestations. Toddlers aged more than 6 months who received exclusive breastfeeding accounted for 45.1% (37 toddlers), while 54.9% (60 toddlers) did not receive exclusive breastfeeding. There was a significant relationship between exclusive breastfeeding and allergic manifestations (p<0.001; PR=0.084; 95% CI=0.021–0.332). ConclusionExclusive breastfeeding acts as a protective factor against allergic manifestations in toddlers.